Sculpturing patterns of plasmonic silver nanoprisms by means of photocatalytic lithography. (16th March 2017) - Panzarasa, Guido; Soliveri, Guido; Marra, Gianluigi; Meda, Laura; Savoini, Alberto; Ardizzone, Silvia; Salvalaggio, Mario
Abstract: The controlled shaping of nanoparticles' morphology is one of the pillars of nanotechnology. Here, we demonstrate that photocatalytic lithography, a technique already proved to be useful in materials science, can act as a dry etching technique for noble metal nanoparticles. Triangular silver nanoprisms are self-assembled on titanium dioxide films and photocatalytically shaped into discoidal particles upon irradiation with near-UV light. The obtained patterned surfaces show a dramatically different surface-enhanced Raman scattering response, suggesting the utility of our approach for the development of sensors. The photocatalytic nature of the particle shaping is demonstrated and a plausible mechanism drawn by performing photocatalysis in different configurations (direct and remote) and by irradiating in different solvents.